Financial Management of MSMEs in Central Lombok Tourism Village - A’ini, Nurul; Lestari, Baiq Anggun Hilendri (Formosa Journal of Multidisciplinary Research, 2024)
The research entitled "Financial Management of MSMEs in Central Lombok Tourism Village" aims to analyze how to manage the finances of MSMEs in Central Lombok Tourism Village and to find out the challenges faced by MSME actors in Central Lombok Tourism Village. This research was conducted in Central Lombok, Pujut area. This research uses a qualitative descriptive approach method. The data collection technique used observation, questionnaire dissemination, and direct interviews with resource persons other sources of books and journals to support research. The number of respondents in this study is 35 MSME business actors in the central Lombok tourist village, Pujut area. This study concludes that the financial management of MSMEs in Central Lombok Tourism Village still needs to be improved, especially in the financial recording that has been eroded. From the results of the research that has been carried out, it can be explained that MSME actors in the tourist village of Central Lombok carry out financial management and planning. However, in simple terms, other MSME actors do not carry out financial management because there is still a lack of knowledge related to financial planning and management. In addition, MSMEs in Central Lombok Tourism Village still do not know about accounting so to run MSMEs, they do not record or make financial reports.